Mass balance of the Greenland Ice Sheet from 1992 to 2018 - Shepherd, Andrew; Ivins, Erik; Rignot, Eric; Smith, Ben; van den Broeke, Michiel; Velicogna, Isabella; Whitehouse, Pippa (Nature (London), 2020)
The Greenland Ice Sheet has been a major contributor to global sea-level rise in recent decades 1 , 2 , and it is expected to continue to be so 3 . Although increases in glacier flow 4 – 6 and surface melting 7 – 9 have been driven by oceanic 10 – 12 and atmospheric 13 , 14 warming, the magnitude and trajectory of the ice sheet’s mass imbalance remain uncertain. Here we compare and combine 26 individual satellite measurements of changes in the ice sheet’s volume, flow and gravitational potential to produce a reconciled estimate of its mass balance. The ice sheet was close to a state of balance in the 1990s, but annual losses have risen since then, peaking at 345 ± 66 billion tonnes per year in 2011. In all, Greenland lost 3,902 ± 342 billion tonnes of ice between 1992 and 2018, causing the mean sea level to rise by 10.8 ± 0.9 millimetres. Using three regional climate models, we show that the reduced surface mass balance has driven 1,964 ± 565 billion tonnes (50.3 per cent) of the ice loss owing to increased meltwater runoff. The remaining 1,938 ± 541 billion tonnes (49.7 per cent) of ice loss was due to increased glacier dynamical imbalance, which rose from 46 ± 37 billion tonnes per year in the 1990s to 87 ± 25 billion tonnes per year since then. The total rate of ice loss slowed to 222 ± 30 billion tonnes per year between 2013 and 2017, on average, as atmospheric circulation favoured cooler conditions 15 and ocean temperatures fell at the terminus of Jakobshavn Isbræ 16 . Cumulative ice losses from Greenland as a whole have been close to the rates predicted by the Intergovernmental Panel on Climate Change for their high-end climate warming scenario 17 , which forecast an additional 70 to 130 millimetres of global sea-level rise by 2100 compared with their central estimate. Three techniques for estimating mass losses from the Greenland Ice Sheet produce comparable results for the period 1992–2018 that approach the trajectory of the highest rates of sea-level rise projected by the IPCC.